Therapeutic adherence in patients with systemic lupus erythematosus: a cross-sectional study - Mazur-Nicorici Lucia; Sadovici-Bobeica Victoria; Garabajiu Maria; Mazur Minodora (Sciendo, 2018)
Introduction. The aim of the research was the study of the adherence to treatment in patients with systemic lupus erythematosus.